A simulation study on the operational stability of an EEV-controlled direct expansion air conditioning system under variable speed operation. (July 2019) - Xia, Yudong; Ding, Qiang; Jiangzhou, Shu; Zhang, Xuejun; Deng, Shiming
Highlights: A dynamic model for a VS DX A/C system was further developed and validated. Temperature sensor dynamics on operational stability were examined. Actual system hunting could be much more serious than what was measured. Sensible and latent cooling capacities on operational stability were investigated. A higher chance to instability at a lower E SHR or a larger TCC. Abstract: Hunting causes a poor operational safety and efficiency of a direct expansion (DX) air conditioning (A/C) system when it is variable speed (VS) operated to output different sensible and latent cooling capacities. An existing dynamic model was further developed by adding the equations for evaluating temperature sensor dynamics and air side operating parameters. After experimentally validated the model, the temperature sensor dynamics and VS operation on stability were numerically examined. Simulation results showed that due to the temperature sensor dynamics, actual system hunting could be much more serious than what was measured, and increasing the thermal resistance between temperature sensor and refrigerant pipeline would mitigate hunting. The mixture-vapor transition point in the DX evaporator would move closer to its exit at a smaller output equipment sensible heat ratio (E SHR) or a larger output total cooling capacity (TCC), consequently, leading to a higher chance to instability.